2000
DOI: 10.1002/1522-726x(200010)51:2<159::aid-ccd6>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac catheterization in diagnosis and management of congenital heart disease in thoracopagus conjoined twins

Abstract: Over the last two decades, surgical separation of thoracopagus conjoined twins has become increasingly feasible. Delineation of the degree of cardiac involvement is essential to establish the feasibility of surgical separation. We describe our experience of cardiac catheterization both in the diagnosis and management of nine sets of thoracopagus twins who presented to a single center over three decades and discuss its role in conjunction with other modern diagnostic modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…Angiography may occasionally still be required if the anatomy severely restricts the echocardiographic windows or if uncertainty about the degree of cardiac fusion persists. [17][18][19] As the resolution of ultrasound has improved, assessing the heart prenatally has become possible at earlier gestations. Diagnostic images have been reported as early as nine weeks' gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Angiography may occasionally still be required if the anatomy severely restricts the echocardiographic windows or if uncertainty about the degree of cardiac fusion persists. [17][18][19] As the resolution of ultrasound has improved, assessing the heart prenatally has become possible at earlier gestations. Diagnostic images have been reported as early as nine weeks' gestation.…”
Section: Discussionmentioning
confidence: 99%
“…The present twins also had only a single fourchambered heart and triple-outlet left ventricle. This also distinguishes our case from the other cases of cardiac fusion in conjoined twins reported in the literature; however, the prognosis was not different (1)(2)(3)(4)(5)(6)(7)(8). Our twins died on the first day due to heart failure and progressive metabolic acidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Anomalies of no hemodynamic significance, such as myocardial bridges with no luminal communications between the two cardiac chambers and the presence of two separate intact conduction systems, is considered less important from a cardiac surgical point of view. 5,6 Pericardial fusion is a minor issue with little surgical risk.…”
Section: At Twin Separationmentioning
confidence: 99%
“…In these cases surgical preparation including the vascular imaging and the placement of monitoring lines, must be made for immediate separation after birth to provide a chance of survival of the pump twin. 5 The use of cardiopulmonary bypass during twin separation is still very limited. Zhong et al recently reported the use of cardiopulmonary bypass for emergency separation of twins (one with complex congenital heart disease) with shared circulation at the age of 24 days.…”
Section: Emergency Separation and Use Of Cardiopulmonary Bypassmentioning
confidence: 99%